REFLEKSI HIBRIDITAS BUDAYA DALAM PANCASILA PADA REALITAS DAN MEDIA SEBAGAI IDENTITAS BANGSA - Rustono Farady Marta (Bricolage : Jurnal Magister Ilmu Komunikasi, 2017)
Studies on the identity are being learned widely, mostly focus on specific groups. The reality we face today is shows the different conditions, because Indonesia has Pancasila as the state philosophy that clearly asserts the motto of "Bhinneka Tunggal Ika". Actually, the spirit that brought ethnic diversity want to be placed in a proper understanding in order to avoid inter-ethnic conflict. The thought has not been led to reform the nation's cultural identity because the implementation is still far from reality. Eddie Lembong (2013) created the „Cross Culture Fertilization‟ concept or „The Cross-fertilization of Culture‟ idea of Paul Monroe (1928), while the form of the pollination contemplated in the process of cross-cultural thinking involves human interaction with a particular context. It needs to be enhanced by adopting the Rosenau‟s idea (2004) about the cultural hybridity in which the establishment of a culture based on the complexity of the dimensions of a person's life. The tangible implementation of cultural hybridity as a mirror of pluralistic nation identity exemplified through observation on the case studies and mass media of a national movie entitled “Tanda Tanya” ("Question Mark"). Keywords: Cultural hybridity, Pancasila, Reality and Media